Microfinance and rural non-farm employment in developing countries - Shyamal Chowdhury (IZA World of Labor, 2017)
The rural non-farm sector plays an important role in diversifying income for rural households in developing countries and has the potential to emerge as a major source of employment. In some cases it has outgrown the agricultural sector, in part due to the expansion of credit through microfinance institutions that are supported by governments, donor agencies, and businesses. However, future expansion of the rural non-farm sector requires increased flexibility in credit contracts, as well as decreasing the cost of credit and the delivery of complementary inputs, e.g. skills training.
Keywords: O12; O16; O17; Q12; 330; microfinance; non-farm employment; developing countries